Promovendo aplicações multimídia interativas com autoria por incorporação de informações de contexto - Melo, Erick Lazaro (Universidade Federal de São Carlos, 2014)
Interactive multimedia applications can turn contents into a much more interesting presentation for users, promote more effective transmission of information, hold the user s attention and eventually promote more satisfaction. However, it is observed that the spread of such applications is very timid. Multimedia content, in general, has been summarized to video and hypermedia documents based on images and text. There are few effective initiatives interactivity with content that benefit from media synchronization. The environment of the Interactive Digital TV offers good potential for exploitation of sync media, however we observe numerous obstacles arising from the conservatism of the industry. The few options available to viewers often end up being ignored. Some reasons may explain the low adoption of interactive multimedia applications: (i) the production of such content is complex - existing authoring tools contribute little to simplify this process, keeping away unskilled designers and developers who choose to use content that can be captured in a simple way (usually video); (ii) the presentation of interactive multimedia content may require specific environments or applications not very widespread or require specialized development; (iii) the content consumption should occur on multiple platforms, making it expensive to develop specific applications for each; (iv) there is a lack of applications widely known to the general public that are really attractive and innovative and that stimulate interactivity. It is believed that this scenario can be changed and interactive multimedia applications can contribute to user satisfaction. It has been hypothesized that attractive interactive multimedia applications can be built with automatic or semiautomatic incorporation, to a leading media, of other media related to it. Related media may be the result of human authorship, with facilitators support, capturing context information, mining the collective interaction in presentation sessions with multiple viewers or combinations of these sources. Based on several published articles, authored or co-authored by the author of this thesis and related to projects managed by him, this text presents efforts and results that contribute to the validation of the hypothesis. These are works that address aspects of multimedia authoring, dissemination of multimedia applications on multiple platforms and media synchronization, all inherent to innovative applications with strong potential to captivate users and serve as catalysts for new applications.
Keywords: Sistemas multimídia; Computação ubíqua; Sincronização; Autoria multimídia; Interação homem-máquina; Ubiquitous computing; Multimedia; Synchronization; Multimedia authoring; Ad-Avoidance; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO